Meta random forest : random forest with simple random forest as base model - Kurniawan, Billy (Nanyang Technological University, 2020)
The abundance of data along with the significant rise of computational power boost the popularity and usage of machine learning in recent decision making and forecasting. Random forest, being one of the current state of the art model, are well known of its high accuracy and efficiency for both classification and regression problems.